Applicability and Theoretical Calculation of Enzymatic Calcium Carbonate Precipitation for Sand Improvement. Issue 4 (20th April 2020) - Sun, Xiaohao; Miao, Linchang; Wu, Linyu
Abstract: Compared with microbially induced calcium carbonate precipitation, enzymatically induced carbonate precipitation is not restricted by microorganisms. Urea concentrations, calcium concentrations, temperature, pH, and reaction days were considered to identify the optimum conditions for sand solidifying tests. For comparison with laboratory tests, a revised equation for the rate of urea hydrolysis and a theoretical model were developed to calculate production rates of calcium carbonate and porosity along sand columns. The results showed that under the same temperature, initial pH, and solute concentration, the pH of leachate, and the strength of sand columns cured with calcium acetate were higher than those cured with calcium chloride. With large particle sizes (1.0–2.0 mm), pH values of leachate were significantly smaller, while the strengths of sand columns with full grading were higher. The revised formula for urea hydrolysis is suitable for the EICP reaction. The theoretically calculated distribution of calcium carbonate is consistent with experimentally obtained results. The one-dimensional mathematical model indicated that the eventual porosity of all sand columns increased slightly along the sand columns and the decreasing range of sand columns cured with calcium acetate was the largest. This study lays a foundation for the application of EICP technology in the future.